PWE-196 Prevalence of Obesity, by Specialty, amongst Inpatients in the South of England. (4th June 2013) - Ambrose, T; Cullen, S; Baker, G; Smith, M; Elia, M; Leach, R; Silva, A De
Abstract : Introduction: Rates of obesity, defined by Body Mass Index (BMI) ≥30kg/m 2, are rising in the United Kingdom. The prevalence, by specialty, of obesity amongst inpatients has not been well studied. Methods: A multicentre, hospital-wide audit across three Trusts in the South of England was performed on a single day to ascertain the prevalence of obese inpatients by specialty. Patients were classified according to specialty (medical, surgical, orthopaedic, intensive care) and allocated a BMI category based on National Institute for Clinical Excellence guidelines (1). Results: 1163 patients were audited (575 male). 778 were medical patients, 222 surgical, 130 orthopaedic, and 33 intensive care. Mean age was 69.3 years with a significant mean age difference between specialties (medical 71.4, surgical 67.7, orthopaedic 61.9, intensive care 60.4) and independent of the hospital studied. 260 patients (22%) had a BMI≥30kg/m 2, of which 103 (9%) had a BMI≥35kg/m 2 . A significant difference in this latter group was observed between specialties (orthopaedic 18%, intensive care 9%, surgical 9%, medical 7% (p < 0.001)). No effect of gender was observed but there was an independent effect of increasing age and higher BMI. Conclusion: Approximately one quarter of inpatients in our multicentre audit were obese according to BMI criteria with 9% significantly obese (BMI≥35kg/m2). Rates of obesity are similar to rates of malnutrition in hospitals. Higher BMI were observed in orthopaedic and intensive care specialties than in medical and surgical. Doctors, nurses and managers should be aware of this variation for training and resource allocation purposes. Disclosure of Interest: None Declared. Reference: Obesity: the prevention, identification, assessment and management of overweight and obesity in adults and children. National Institute for Health and Clinical Excellence. December 2006.